The Impact of a 1.1 MWp PV Rooftop Integration in Medium Voltage Distribution Networks - Prasetya, Candra Agung; Sudiarto, Budi (Universitas Indonesia, 2023)
A high penetrating the capacity of Rooftop PLTS has an impact on the performance of distribution network operations and the prior technical studies only using simulation. This paper examines the impact of integrating a 1.1 MWp PV Rooftop into the medium voltage distribution network, involves a comparison between simulation data obtained using the ETAP software, before and after integration, compared with direct measurements. The results indicate improvements in the distribution operating performance. Following the integration, there was a 0.05% increase in voltage levels, a 0.06% increase in short circuit current, a 1.25% reduction in network losses, up to 8.9% harmonics current, up to 0.14% harmonics voltage, and a 0.28% decrease in power factor, as observed at both the substation and the network, they are in accordance with the measurement results.